“Budi Pekerti” as a Civil Religion: The Paradox of Schools in Shaping Moral Exemplar - Wahyuni, Indah (The Eastasouth Journal of Social Science and Humanities, 2025)
This article critically examines the practice of "Budi Pekerti" (character education) in schools in Batam, Indonesia, by analyzing it as a form of civil religion and symbolic ritual. Drawing on personal experiential reflection and theoretical frameworks from Clifford Geertz, Émile Durkheim, Pierre Bourdieu, and Jean Baudrillard, the study reveals a fundamental paradox: instead of fostering genuine morality, the ritualized and compulsory nature of these activities often produces false obedience and performative conformity. The analysis identifies key failures, including the erosion of intrinsic meaning (ritual failure), the prioritization of administrative compliance over ethical internalization, and the reinforcement of social hierarchies and biases. Furthermore, for Generation Z, these practices are often perceived as empty liturgies, leading to disenchantment. The study concludes that the institutionalization of moral values through coercive, standardized rituals results in a "pseudo-morality," where symbols replace substance and performance trumps authentic ethical commitment. It argues for a reimagining of moral education that prioritizes critical reflection, personal autonomy, and authentic lived experience over rigid ceremonial formalism.